Effects of urban forest fragmentation on native mammals in Selangor, Malaysia - Tee, Sze Ling (2018)
Rapid urbanisation has caused major deforestation and habitat fragmentation in the tropics. Yet, the ecological impacts of forest fragmentation on biodiversity are understudied in urban landscapes particularly those that are heavily surrounded by anthropogenic activities. To date, little is known about the conservation value of the patches for maintaining mammalian biodiversity, as each species requires different habitat characteristics. This study uses the camera trapping method to (1) determine the composition of medium- to large-sized mammal species present; (2) identify the dominant species of mammalian community; (3) compare the mammal species composition; and (4) determine the key habitat variables that affect the mammal species richness in three forest patches: AHFR, BCFR, and BFR and one contiguous forest, SLFR. All forest areas are located in Selangor, the most developed and urbanised state in Malaysia. The study was conducted from September 2016 to October 2017 by deploying 30 wildlife cameras at each forest area. A total number of 19 mammal species comprising 11 omnivores, four herbivores, three carnivores and one insectivore from 120 sampling points were recorded. SLFR had the highest number of species compared to the urban forest patches. Only three conservation priority species were recorded, namely the Sunda Pangolin in AHFR and BFR, the Asian Tapir in BCFR and SLFR and the White-handed Gibbon was recorded in the SLFR. Top predators such as Tigers and Leopards were completely absent from the forest patches. This was reflected by hyper-abundance of wild boars. In SLFR, Eurasian Wild Boar, Barking Deer, Long-tailed Macaque and Lesser Mousedeer represented 93% of the species composition. While in AHFR, 98% of the majority species composition made up of Pig-tailed Macaque and Lesser Mousedeer. Eurasian Wild Boar and Pig-tailed Macaque represented 91% and 94% of the species composition in BCFR and BFR respectively. Omnivorous species was the most common found in all study areas may explained by their high tolerance towards modified environments. The mammal species richness responded positively with the number of trees with DBH less than 5 cm, trees with DBH more than 50 cm,and the number of dead standing trees. Sufficiency of food resources provided by trees with DBH less than 5 cm, hiding places provided by trees with DBH more than 50 cm, and food resources and nesting sites provided by dead standing trees are crucial for every species’ persistency. Improving the connectivity between the urban forest patches and continuous forest may be impossible due to land scarcity and urban expansion. This is true particularly for facilitating the movement of ground-dwelling and arboreal mammals. Hence, government stakeholders are recommended to take intervention measures such as species reintroduction and restocking the wild populations in the urban forest patches.